Sodicity affects growth, yield and cation composition of fennel (Foeniculum vulgare Mill.) - Garg, V K (Journal of Spices and Aromatic Crops, 2012)
Field trials were conducted at Banthra, Lucknow, (Uttar Pradesh) to study the effect of sodicity on growth, yield and cation composition of fennel (Foeniculum vulgare mill.) grown in a Typic Natrustalf. The treatments included five exchangeable sodium percentage (ESP) levels (10, 20, 30, 40 & 50) and four genotypes viz., HF-107, NDF-9, Local BRS and NDF-7. An adverse effect of sodicity was observed on emergence of secondary branches and seed setting causing decrease in seed yield. The variety HF-107 produced the highest seed yield (1956 kg ha-1) followed by Local BRS (1709 kg ha-1), NDF-9 (1577 kg ha-1) and NDF-7 (1078 kg ha-1). The cation composition of stover revealed Na inclusion mechanism with narrow K/Na and Ca/Na ratios. The study further revealed that the crop can tolerate medium level of sodicity (ESP 30).